Influence of nanohydroxyapatite surface properties on Staphylococcus epidermidis biofilm formation - J. Barros (2014)
Nanohydroxyapatite (nanoHA), due to its chemical properties, has appeared as an exceptionally promising bioceramic to be used as bone regeneration material. Staphylococcus epidermidis have emerged as major nosocomial pathogens associated with infections of implanted medical devices. In this work, the purpose was to study the influence of the nanoHA surface characteristics on S. epidermidis RP62A biofilm formation. Therefore, two different initial inoculum concentrations (C-i) were used in order to check if these would affect the biofilm formed on the nanoHA surfaces. Biofilm formation was followed by the enumeration of cultivable cells and by scanning electron microscopy. Surface topography, contact angle, total surface area and porosimetry of the biomaterials were studied and correlated with the biofilm data. The surface of nanoHA sintered at 830celcius (nanoHA830) showed to be more resistant to S. epidermidis attachment and accumulation than that of nanoHA sintered at 1000celcius (nanoHA1000). The biofilm formed on nanoHA830 presented differences in terms of structure, surface coverage and EPS production when compared to the one formed on nanoHA1000 surface. It was observed that topography and surface area of nanoHA surfaces had influence on the bacterial attachment and accumulation. C-i influenced bacteria attachment and accumulation on nanoHA surfaces over time. The choice of the initial inoculum concentration was relevant proving to have an effect on the extent of adherence thus being a critical point for human health if these materials are used in implantable devices. This study showed that the initial inoculum concentration and surface material properties determine the rate of microbial attachment to substrata and consequently are related to biofilm-associated infections in biomaterials.